Narratives of family transition during the first year post-head injury: perspectives of the non-injured members - Whiffin, Charlotte Jane; Bailey, Christopher; Ellis-Hill, Caroline; Jarratt, Nickey; Hutchinson, Peter (Wiley, 2015)
Aim